Sufficient sleep and its contributing factors among high school students during the COVID-19 pandemic: results from adolescent behaviors and experiences survey - Zhengyang Chen; Ruili Li; Yuexi Liu; Qiguo Lian (Frontiers Media S.A., 2024)
BackgroundThe COVID-19 pandemic has caused profound changes in adolescent lives, including school closures, social isolation, family economic hardship, and sleep schedule. We aimed to assess the risk and protective factors of sufficient sleep among adolescents during COVID-19.MethodsWe conducted secondary analysis based on the cross-sectional school-based Adolescent Behaviors and Experiences Survey in 2021 (n = 7,705). The ABES collected information on health-related experiences and behaviors during COVID-19. The outcome was sufficient sleep (eight and more hours of sleep on the average school night). The contributing factors included demographic, mental health, and adverse experiences indicators. We estimated the prevalence of sufficient sleep within each factor, and examined their associations using Chi-square test. We further investigated the contributing factors of sufficient sleep using multivariate logistic regression and reported the adjusted odds ratios (AORs) and 95% confidence intervals (CIs).ResultsDuring January-June 2021, 23.5% of the U.S. high school students reported getting sufficient sleep. The multivariate logistic regression indicated that younger age (AOR, 2.04; 95%CI, 1.59-2.62), heterosexual identity (AOR, 1.61; 95%CI, 1.19-2.18), no poor mental health during the past 30 days (AOR, 1.37; 95%CI, 1.03-1.82), no persistent feelings of sadness or hopelessness (AOR, 1.34; 95%CI, 1.09-1.66), no food and nutrition insecurity (AOR, 1.47; 95%CI, 1.17-1.85), never been abused by a parent emotionally (AOR, 1.38; 95%CI, 1.16-1.64), and no schoolwork difficulty (AOR, 1.24; 95%CI, 1.01-1.51) were associated with sufficient sleep.ConclusionWe estimated the national prevalence of adolescent sufficient sleep during the COVID-19 pandemic and found that younger students, sexual heterosexual students, and students without certain mental health conditions or adverse experiences are at higher likelihood of sufficient sleep. These findings can help develop effective interventions on sleep duration in the response to a possible future pandemic caused by Disease X.